Ellow: The mobile application for electricity consumption - Touma, Smedra; Issa, Firel (My University, 2023)
This project pursued the creation of a mobile application for managing electricity usage remotely for two distinct groups, the elderly and those with OCD. During the study, the focus narrowed to individuals with OCD. The mobile application is the creation of a system which acts as a controller, namely for reducing the electricity consumption within homes, with a special focus on people with OCD. The user was able to switch their electrical devices on/off when they were not at home. The application provided statistical data, on consumption over days, months, and years. A bar code “QR code” was connected to each electrical device. This was made to add the scanned device to the application. In the application, there was a feature that enabled users to have anonymous conversations with therapists and engage in chats with other users who share a common diagnosis of OCD. The project carried valuable insights from an expertise group, in a company called R.I.S.E. Low and high-fidelity prototypes were done together with surveys, questionnaires, and usability tests. Interviews were conducted and the Swedish OCD Association discussions were recorded. To achieve success in the project, the team followed the five stages of the design thinking process: Empathize, Define, Ideate, Prototype, and Test. Each stage employed different methodologies and techniques to ensure thorough exploration and effective problem-solving. The project resulted in a mobile application, called Ellow. User observations revealed the importance of easy-to-use mobile applications for both the elderly and individuals with OCD. Collaboration with psychologists enhanced the prototype, emphasizing the need for advanced features to address OCD concerns. Legal considerations highlighted the challenges in creating technology solutions for OCD, emphasizing the importance of evolving legal systems. Overall, the study emphasizes the significance of tailoring applications to diverse user needs and experiences in symptom management for OCD.
Keywords: Mobile application; QR code; OCD; electricity consumption; Interaction Design; disability